2018
DOI: 10.1021/jacs.8b10047
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Exosomes as Nanoscale Controllers of Cellular Immunity

Abstract: Exosomes are naturally occurring membranous vesicles secreted by various types of cells. Given their unique and important biological and pharmacological properties, exosomes have been emerging as a promising form of nanomedicine acting via efficient delivery of endogenous and exogenous therapeutics. Here we explore a new concept of utilizing endogenously derived exosomes as artificial controllers of cellular immunity to redirect and activate cytotoxic T cells toward cancer cells for killing. This was achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
166
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(167 citation statements)
references
References 41 publications
1
166
0
Order By: Relevance
“…Brain and muscle targeting was achieved by bioengineering a fusion protein of Lamp2b with neuron-specific rabies viral glycoprotein (RVG) peptide and muscle-specific peptide on the surface of EVs, respectively (Alvarez-Erviti et al, 2011). The second modification method was demonstrated by Cheng et al (2018a) who engineered anti-CD3 and anti-EGFR on the surface of the exosomes allowing a cross-link of T cells and EGFR þ cancer cells and eliciting potent antitumor immunity. The third way to endow EVs targetability was illustrated by Hong et al (2018) who showed that hyaluronidase engineered exosomes could degrade tumor extracellular matrix and enhance the permeability of T cells and drugs in the tumor milieu.…”
Section: Cell Targeting Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain and muscle targeting was achieved by bioengineering a fusion protein of Lamp2b with neuron-specific rabies viral glycoprotein (RVG) peptide and muscle-specific peptide on the surface of EVs, respectively (Alvarez-Erviti et al, 2011). The second modification method was demonstrated by Cheng et al (2018a) who engineered anti-CD3 and anti-EGFR on the surface of the exosomes allowing a cross-link of T cells and EGFR þ cancer cells and eliciting potent antitumor immunity. The third way to endow EVs targetability was illustrated by Hong et al (2018) who showed that hyaluronidase engineered exosomes could degrade tumor extracellular matrix and enhance the permeability of T cells and drugs in the tumor milieu.…”
Section: Cell Targeting Propertiesmentioning
confidence: 99%
“…EVs are enriched in blood, saliva, and other biological fluids (Thery et al, 2002;Barile & Vassalli, 2017), carrying and delivering diverse biomolecules from their parent cells to receptor cells (Thakur et al, 2014;Thery, 2015). A growing body of evidence has shown that EVs are important mediators of intercellular communication and thus play significant roles in physiological and pathological processes, including stem cell maintenance, tissue repair, immune modulation, and tumor growth (Valadi et al, 2007;Thakur et al, 2014;Cheng et al, 2018a;He et al, 2018). As 'molecule carrier', EVs may serve as novel tools for various therapeutic and diagnostic purpose (EL Andaloussi et al, 2013;Ohno et al, 2016), such as anti-tumor therapy (Poggio et al, 2019), immune-modulatory (Buzas et al, 2014), and drug delivery (Gudbergsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Exosomes are a class of lipid bilayer extracellular vesicles that are endogenously secreted by almost all types of mammalian cells, with a diameter distribution of 30-100 nm and respond for cell-cell communication through transporting molecules from parent cells to recipient cells. [10][11][12] In the view of naturally derived nanocarriers, exosomes have been recognized as excellent nanovehicles for drug delivery due to their low biotoxicity and diverse biofunctions such as immune privilege, cargo protection, and most importantly stringent biological barriers penetrating ability. [13][14][15][16][17] It has been reported that exosomes exhibit intrinsic tissue or cell-targeting properties owing to their particular surface structures like tetraspanins and integrins.…”
Section: Doi: 101002/advs201801899mentioning
confidence: 99%
“…In addition to CART-cell immunotherapy,other immune cells [27] and cell-derived materials,s uch as microvesicles, exosomes,a nd membranes,h ave been used to improve immunotherapy.A part from their intrinsic functions,c ell-derived vesicles can be developed with exogenous abilities by chemical modification and bioengineering. [28] Fore xample, Wang et al demonstrated that engineered platelets can drastically inhibit tumor recurrence and metastasis after surgical removal of the primary tumor. [29] Thea uthors decorated platelets with PD-L1 antibodies through maleimide-based chemical ligation.…”
Section: Cell-based Materialsmentioning
confidence: 99%